SURVEI MINAT DAN MOTIVASI DALAM PERMAINAN BOLAVOLI PADA SISWA SMP NEGERI 1 SUNGGUMINASA KABUPATEN GOWA - Ramli, Ramli; Hakim, Hikmad (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2020)
This research is a type of descriptive research. This study aims to determine; 1) Interest in learning in volleyball games for students at SMP Negeri 1 Sungguminasa, Gowa Regency, 2) Motivation for learning to play volleyball in students at SMP Negeri 1 Sungguminasa, Gowa Regency. The population is all students of SMP Negeri 1 Sungguminasa, Gowa Regency. The sample used was grade VII students. L Sungguminasa 1 Public Middle School as many as 30 people. The technique of determining the sample is to use saturated samples. The data analysis technique used is descriptive frequency analysis. The results showed that: 1) Interest in learning in volleyball games at students of SMP Negeri I Sungguminasa Gowa Regency in the high category or at 74.44%, 2) Motivation of learning in volleyball games at SMP Negeri 1 Sungguminasa students in Gowa Regency in the high category or equal to 76.67%.